Європейські підходи до оцінки сталої міської мобільності - Кристопчук, Михайло (ТзОВ «Галицька видавнича спілка», 2021)
In cities, the growing number of private vehicles burdens the infrastructure and consequently transport systems become saturated. A paradigm shift in transport policy is necessary to achieve sustainable mobility.
European approaches to the assessment of sustainable urban mobility
Keywords: 656.072